Concurrent emergence of exotic whitefly incursions on arecanut (Areca catechu L.) in India - Thube, Shivaji Hausrao; Josephrajkumar, A.; Pandian, R. Thava Prakasa; Saneera, E.K.; Bhavishya; Babu, Merin; Rajkumar; Jose, C.T. (Journal of Plantation Crops, 2021)
Field incidence of exotic whitefly complex comprising two Neotropical nesting whiteflies viz., Paraleyrodes bondari Peracchi and Paraleyrodes minei Iaccarino, in association with invasive rugose spiralling whitefly Aleurodicus rugioperculatus Martin and native areca whitefly, Aleurocanthus arecae David & Manjunatha, on arecanut was reported from Karnataka, India during 2020. These arecanut palms were previously infested by A. arecae which was earlier reported from Karnataka during 2003. To our knowledge, this is the first report on the infestation of P. bondari and P. minei on arecanut as highlighted in this current investigation. Morphological identification based on pupal taxonomy and male genitalia as well as molecular characterization of the mitochondrial cytochrome oxidase I (COI) gene confirmed the identity of nesting whiteflies. The Bondar’s nesting whitefly, P. bondari is the most predominant whitefly species with 87.5 per cent active colonies followed by the nesting whitefly, P. minei (13.64%) and the rugose spiralling whitefly, A. rugioperculatus (6.25%). Co-occurrence of these three non-native whitefly species on arecanut in synergy with the native A. arecae indicates a kind of competitive regulation of one species over the other upsetting biodiversity. Due to the polyphagous nature of the pest coupled with increased trade and transport in a climate change scenario, this whitefly complex may become a serious threat to arecanut production in India and elsewhere. This requires strict quarantine protocols to avert its spread to other arecanut growing areas.